2018
DOI: 10.3390/met8030160
|View full text |Cite
|
Sign up to set email alerts
|

Characterization on the Microstructure Evolution and Toughness of TIG Weld Metal of 25Cr2Ni2MoV Steel after Post Weld Heat Treatment

Abstract: The microstructure and toughness of tungsten inert gas (TIG) backing weld parts in low-pressure steam turbine welded rotors contribute significantly to the total toughness of the weld metal. In this study, the microstructure evolution and toughness of TIG weld metal of 25Cr2Ni2MoV steel low-pressure steam turbine welded rotor under different post-weld heat treatment (PWHT) conditions are investigated. The fractography and microstructure of weld metal after PWHT are characterized by optical microscope, SEM, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These results support those proposed by Park et al [33], who found that for a Ni-Mo-Cr system, adding 1% Cr enhances carbide precipitation and coarsening as predicted by thermo-calc analysis (Fig. 10), which is reported as toughness reducing agent in the Charpy-V impact test [8,33,34]. Figure 11 shows that PWHT did not significantly reduce microhardness.…”
Section: Resultssupporting
confidence: 87%
“…These results support those proposed by Park et al [33], who found that for a Ni-Mo-Cr system, adding 1% Cr enhances carbide precipitation and coarsening as predicted by thermo-calc analysis (Fig. 10), which is reported as toughness reducing agent in the Charpy-V impact test [8,33,34]. Figure 11 shows that PWHT did not significantly reduce microhardness.…”
Section: Resultssupporting
confidence: 87%
“…A total of 22 papers cover a ranger of structural metals and alloys. The major portion of these papers is focused on the mechanisms of microstructure evolution and the mechanical properties of metallic materials subjected to various thermo-mechanical, deformation, or heat treatments [1][2][3][4][5][6][7][8][9][10][11][12]. Another large portion of the studies is aimed on the elaboration of alloying design of advanced steels and alloys [13][14][15][16].…”
Section: Contributionsmentioning
confidence: 99%
“…Those readers interested in structural steels may learn much from comprehensive investigations of microstructural changes and their effect on mechanical properties caused by plastic working and heat treatment of diverse steel types [2,7,8,10,12,15,16,[19][20][21][22]. Two of these papers [7,12] present experimental/simulation results of mechanical behavior of high-Mn TWIP steels, which have recently aroused a great interest among material scientists and engineers because of outstanding strengthductility combination inherent in such steels.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations